AQUISITION ACTIVITIES IN ENGLISH FOREIGN LANGUAGE (EFL) TEACHING - Farida Hanim Saragih; Syamsul Bahri (BAHAS, 2015)
This paper aims at discussing the use of four possible ways to conduct acquisition activities in English Foreign Language (EFL) classroom teaching and focuses on some of the appealing uses of vivid linking, story retelling, self directed statement and role playing in intensive reading, and on how language teachers could exploit them in their classes. These ways of teachers to use the acquisition activities could be considered by the language teachers in teaching intensive reading. This article implies that language acquisition and language learning are interrelated and mutually supplementary to develop competence in EFL, and this paper attempts to present acquisition activities by providing an overview of some of the interesting uses of vivid linking, story retelling, self directed statement and role playing, and suggesting ways of exploiting them in intensive reading classroom. Keywords: acquisition, intensive reading, vivid linking, story retelling, self directed statement and role playing